132k views
2 votes
Which set of steps shows the solution to the equation 3y = −9? (5 points) y = −9 − 3; y = 6 y = −9 ÷ 3; y = −3 y = −9 ÷ (−3); y = 3 y = −9 − (−3); y = −6

User MBria
by
5.4k points

2 Answers

3 votes

Answer:

B.y=-9divide 3:y=-3

Explanation:

i took the test on flv cause im a student and i got it right

User Henrique Barcelos
by
5.5k points
4 votes

Answer:

y = −9 ÷ 3; y = −3

Explanation:

We have the equation
3y=-9 and we want to solve it.

Let's do it step-by-step.

Step 1. Remember that to solve an equation, we should isolate the variable in the left side of the equation. Since the number 3 is multiplying
y, we need to get rid of that 3 by performing the inverse operation of multiplication. The inverse operation of multiplication is division, so to get rid of the 3 in
3y, we need to divide it by 3. But remember that every operation performed in one side of the equation should be performed in the other side as well (to keep the things equal), so we need to divided 9, in the right side, by 3 as well.

To synthesize, the first step to solve our equation is divide both sides by 3:


3y=-9


(3y)/(3) =(-9)/(3)


y=(-9)/(3)

y = −9 ÷ 3

Step 2. The only thing left is divide -9 by 3 to find the value of
y and solve our equation:


y=(-9)/(3)


y=-3

y = −3

We can conclude that the set of steps that show the solution of 3y = −9 is y = −9 ÷ 3; y = −3

User Openmobster
by
5.9k points